The occurrence of Dryocoetes krivolutzkajae (Coleoptera: Curculionidae: Scolytinae) in Canada: a potential pest of cultivated roseroot (Crassulaceae). Issue 6 (24th April 2015) - Cognato, Anthony I.; Cuerrier, Alain; Ampong-Nyarko, Kwesi; Hermanutz, Luise; Mardones, Vanessa
Abstract: Dryocoetes krivolutzkajae Mandelshtam (Coleoptera: Curculionidae), a scolytine bark beetle previously known only from the Kamchatka Peninsula, Russia was discovered in Labrador and New Brunswick, Canada. It is unknown whether the Canadian populations represent an introduction or the natural range of D. krivolutzkajae. The habit of this beetle is particular because it is one of the few scolytines that complete their lifecycle within herbaceous roots. This species feeds on the rhizomes of Rhodiola rosea Linnaeus (Crassulaceae) an important natural medicinal plant. Currently it is unknown if, and how rhizome infestation affects the active chemical constituents. The impact of D. krivolutzkajae on the quantity and quality of R. rosea rhizomes requires study.